Institutionalizing policies for persons with disabilities in Marikina City - Catura, Severo S. (Quezon City: Asian Center, University of the Philippines Diliman, 2022)
This study is about the relationship between local inclusive development initiatives and the person with disability in an urban setting, specifically Marikina City. By adopting the social model of disability, it describes the conditions of persons with disability in the said city and how local inclusive development has been sought to be achieved among them. It reviews available local government and community resources to unearth patterns, if any, that are in pursuit of the improvement of the productive and creative capability of persons with disability. Factors that shape the inclusive outcome of local initiatives are sought to surface the ways and means to recommend the further institutionalization of programs for persons with disability.
Includes bibliographical references.
Thesis (Master of Arts in Philippine Studies)
Keywords: People with disabilities -- Services for -- Marikina City (Philippines)